1999
DOI: 10.1016/s0002-9440(10)65474-0
|View full text |Cite
|
Sign up to set email alerts
|

Stromal-Cell Derived Factor Is Expressed by Dendritic Cells and Endothelium in Human Skin

Abstract: Stromal-cell derived factor or SDF-1 is a CXC chemokine constitutively expressed by stromal bone marrow cell cultures that binds to the G-protein-coupled receptor CXCR4. SDF-1/CXCR4 represents a unique, nonpromiscuous ligand/receptor pair that plays an essential role in prenatal myelo- and lymphopoiesis as well as in cardiovascular and neural development. SDF-1 prevents entry of CXCR4-dependent (X4) HIV viruses in T lymphocytes, by binding and internalizing CXCR4. The expression pattern of SDF-1 protein in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
191
2
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(210 citation statements)
references
References 40 publications
14
191
2
3
Order By: Relevance
“…Roles for the SDF-1/CXCR4 interaction, other than normal homeostasis and development, have been reported recently in pathologic conditions such as rheumatoid arthritis (RA) , inflammatory skin diseases (Pablos et al, 1999), and skin wound healing (Fedyk et al, 2001). In the RA synovium, SDF-1 was expressed in cells with a fibroblastic appearance, whereas it was not expressed in the synovium of osteoarthritis.…”
Section: Scdf-1 In Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Roles for the SDF-1/CXCR4 interaction, other than normal homeostasis and development, have been reported recently in pathologic conditions such as rheumatoid arthritis (RA) , inflammatory skin diseases (Pablos et al, 1999), and skin wound healing (Fedyk et al, 2001). In the RA synovium, SDF-1 was expressed in cells with a fibroblastic appearance, whereas it was not expressed in the synovium of osteoarthritis.…”
Section: Scdf-1 In Liver Diseasesmentioning
confidence: 99%
“…Pablos et al (1999) reported that SDF-1 was expressed in fibroblasts close to or within dermal inflammatory infiltrates of inflammatory skin diseases, whereas it is confined to endothelial cells, pericytes, and dendritic cells, not fibroblasts, in normal human skin, suggesting that SDF-1 gene expression of skin fibroblasts is upregulated by proinflammatory stimuli. In contrast, Fedyk et al (2001) demonstrated that SDF-1 production by skin fibroblasts is inhibited by cytokines such as IL-1 and TNF-␣.…”
Section: Scdf-1 In Liver Diseasesmentioning
confidence: 99%
“…1-3 SDF-1 is constitutively expressed by stromal, endothelial, dendritic, and other cells. [4][5][6] It stimulates the motility of hematopoietic cells, lymphocytes, and monocytes, 7,8 thymocytes, 9 and mediates leukocyte adhesion to the vascular endothelium. 10 SDF-1 also influences the development of microglia, astrocytes, and neurons.…”
Section: Introductionmentioning
confidence: 99%
“…By using a CXCR4 antagonist treatment, Kabashima et al demonstrated that the ligation of CXCR4 to its ligand CXCL12 plays also a key role for DC migration into draining lymph nodes in vivo. CXCL12 is expressed by stromal cells in the medulla of lymph nodes, in the red pulp of the spleen, in the bone marrow, and by skin endothelial cells [27,28]. Human DC themselves may also express CXCL12 [28], which has potent chemoattractant properties for lymphocytes expressing CXCR4 [29], suggesting that DC could also play a critical role in lymphocytic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 is expressed by stromal cells in the medulla of lymph nodes, in the red pulp of the spleen, in the bone marrow, and by skin endothelial cells [27,28]. Human DC themselves may also express CXCL12 [28], which has potent chemoattractant properties for lymphocytes expressing CXCR4 [29], suggesting that DC could also play a critical role in lymphocytic circulation.Using a Boyden chamber assay, a significantly increased migratory capacity of DC activated by VLP or LPS was demonstrated in the presence of CXCL12. The recruitment of DC stimulated by VLP or LPS was also more important in the presence of HFM.…”
mentioning
confidence: 99%